At the Intersection of the Artistic and the Practical - Pearse, Lukas (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Artistic Director Lukas Pearse describes the impact of the COVID-19 pandemic on the Upstream Music Association in Halifax, Nova Scotia.